The anticancer properties, cell-cycle cytotoxicity and apoptosis of cissus rotundifolia, trema orientalis, and buddleja polystachya with ocular applications - Ali Hendi Alghamdi; Aimun A.E. Ahmed; Mahadi bashir; Haidar abdalgadir; Asaad khalid; Ashraf N. Abdalla; Mohamed E. elzubier; Riyad almaimani; Bassem refaat; Khalid alzahrani; Saleh MS. alghamdi; Sheraz gul (Phytomedicine Plus)
Background: Buddleja polystachya, Trema orientalis, and Cissus rotundifolia were applied locally for various ocular purposes, while receiving few scientific evaluations. Purpose: This study aimed to screen the anticancer properties and determine the cell-cycle cytotoxicity and apoptotic activity of the most promising plant extract. Methods: In this study, MTT assays with MCF7 (human breast adenocarcinoma), HT29 (human colorectal adenocarcinoma) and HepG2 (human liver adenocarcinoma) were used. In addition to MRC5 (normal human foetal lung fibroblast) was carried out for preliminary activity screening and selectivity. The most promising extract was subjected to GC–MS analysis to determine the phytochemical composition. Additionally, a clonogenic assay was performed to measure tumor cell survival and subsequent proliferative capacity after drug exposure was conducted for the most active extract(s) and finally western blotting was used to determine the expression change of the two selected proteins (survivin and CCND1) in order to determine the exact mechanistic features of the most promising plant extract. Results: The six extracts showed variable IC50 values ranging from 1.77 to - 40.97 μg/mL. The most active extracts were C. rotundifolia coded as (stem; BEP-03A and leaves; BEP-03B) on HepG2 cells and showed ∼ 4 and 8 fold selectivity compared to normal MRC5 cells. Both extracts showed a dose-dependent clonogenic effect on HepG2 cells, which was comparable to the effect of doxorubicin. The extract (BEP-03B) caused a significant decrease in the expression of survivin and CCND1 compared to the control GAPDH at its highest dose (12 µg/mL). The GC–MS chromatogram of the leaf of C. rotundifolia extract (BEP-03B) revealed the presence of 17 compounds, as the main phytoconstituents representing 57.5 % of the total compounds present in BEP-03B Three steroidal components (12, 14 and 15) were the main components, while compound stigmast-5-en-3-ol (compound 15) was the main component. Conclusions: Leaves of Cissus rotundifolia (Forssk.) Vahl, possess a significant cytotoxic effect and it may produce this effect, through apoptosis induction, perturbation, and disruption of the cell cycle. The detected phytoconstituents in the plant extract might be involved in the tested cytotoxic activity and its molecular apoptotic mechanism. Future studies are required to isolate the active ingredient(s) and confirm the therapeutic application(s).